Interregional Newborn Hearing Screening via Telehealth in Ghana - Ameyaw, Graham Amponsah; Ribera, John; Anim-Sampong, Samuel (Journal of the American Academy of Audiology, 2019)
Newborn hearing screening is a vital aspect of the Early Hearing Detection and Intervention program, aimed at detecting hearing loss in children for prompt treatment. In Ghana, this kind of pediatric hearing service is available at only one health care facility located in the Greater Accra Region. The current practice in effect has virtually cut-off infants in the other regions from accessing hearing screening and other pediatric audiological services. This has prompted a study into alternative methodologies to expand the reach of such services in Ghana. The present study was designed to assess the feasibility of using telehealth to deliver newborn hearing screening across Ghana.To assess the feasibility of using telehealth to extend newborn hearing screening services across the ten regions of Ghana.A correlational study was designed to determine the extent of association between test results of telehealth and the conventional on-site methods (COMs) for conducting newborn hearing screening. The design also allowed for testing duration between the two methods to be compared.Fifty infants from the Brong-Ahafo Regional Hospital (BARH) were enrolled. The infants aged between 2 and 90 days were selected through convenience sampling. There were 30 males and 20 females.Newborn hearing screening using distortion product otoacoustic emissions were performed via telehealth. By adopting the synchronous telehealth model, an audiologist located at the Korle-Bu Teaching Hospital conducted real-time hearing screening tests over the internet on infants who were at the BARH. The former and latter hospitals are located in the Greater Accra and the Brong-Ahafo Regions, respectively. As a control, similar hearing screening tests were conducted on the same infants at BARH using the conventional face-to-face on-site hearing screening method.The test results and testing duration of the telehealth method and the conventional on-site approach were compared and subjected to statistical analysis. Here, the Spearman’s correlation coefficient (rs) was used to determine the level of correlation between the test results, whereas the paired t-test statistic was used to test the level of significance between the testing duration of the two methods.Analysis of the test results showed a significantly high positive correlation between the telehealth and the COMs (rs = 0.778, 0.878, 0.857, 0.823, p < 0.05 @ 2.0, 3.0, 4.0, and 5.0 kHz respectively). Also, the difference in testing duration of the two methods was not statistically significant [t(99) = 1.309, p > 0.05]. The mean testing duration (in seconds) of telehealth was 27.287 (standard deviation = 27.373) and that of the COM was 24.689 (standard deviation = 27.169).The study showed the feasibility of establishing an interregional network of newborn hearing screening services across Ghana using telehealth. It is more efficient to deploy telehealth for pediatric hearing services than to have patients travel many hours to the Greater Accra Region for similar services. Poor road network, high transportation costs, and bad weather conditions are a few of the reasons for avoiding long distance travel in Ghana.
Keywords: Africa; audiology; Brong-Ahafo Regional Hospital; childhood hearing loss; distortion product otoacoustic emissions; distortion product otoacoustic emissions screening; Ghana; hearing screening; infant hearing screening; Korle-Bu Teaching Hospital; newborn hearing screening; otoacoustic emissions screening; sub-Saharan Africa; synchronous telehealth model; tele-audiology; telehealth; telemedicine